Phase shift mask blank, phase shift mask, and method for manufacturing a phase shift mask
Patent Information
- Application Number
- KR1020237007987
- Authority / Receiving Office
- KR · KR
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2020-09-08
- Filing Date
- 2021-09-07
- Publication Date
- 2026-09-22
- Estimated Expiration
- 2041-09-07
Smart Images

Figure 112023025748803-PCT00001_ABST
Abstract
Description
Technology Field
[0001] The present invention relates to a phase shift mask blank, a phase shift mask, and a method for manufacturing a phase shift mask used in the manufacture of semiconductor devices, etc. Background Technology
[0002] In recent years, in semiconductor processing, particularly due to the high integration of large-scale integrated circuits, the miniaturization of circuit patterns has become necessary, and there is a growing demand for technology to miniaturize wiring patterns and contact hole patterns that constitute the circuit. Consequently, the exposure light source used in the manufacture of semiconductor devices and the like is becoming shorter in wavelength, moving from the KrF excimer laser (wavelength 248 nm) to the ArF excimer laser (wavelength 193 nm).
[0003] In addition, as a mask that improves wafer transfer characteristics, there is, for example, a phase shift mask. In a phase shift mask, it is possible to adjust both the phase difference and the transmittance such that the phase difference between the ArF excimer laser light passing through the transparent substrate and the ArF excimer laser light passing through both the transparent substrate and the phase shift film (hereinafter simply referred to as "phase difference") is 180 degrees, and the ratio of the amount of light of the ArF excimer laser light passing through both the transparent substrate and the phase shift film to the amount of light of the ArF excimer laser light passing through the transparent substrate (hereinafter simply referred to as "transmittance") is 6%.
[0004] For example, when manufacturing a phase shift mask with a phase difference of 180 degrees, a method is known in which the thickness of the phase shift film is set so that the phase difference is around 177 degrees, and then the phase shift film is dry-etched with a fluorine-based gas while simultaneously processing a transparent substrate to a thickness of about 3 nm to finally adjust the phase difference to around 180 degrees.
[0005] In the case of a phase shift mask to which exposure light with a wavelength of 200 nm or less is applied, exposure may cause foreign substances called "haze" to gradually form, grow, and become visible on the mask, making the mask unusable. In particular, when the phase shift film is a film composed of silicon, transition metals, and light elements such as oxygen or nitrogen, foreign substances may occur on the surface of the phase shift film.
[0006] As for techniques for suppressing haze, there are, for example, those described in Patent Documents 1 and 2.
[0007] However, the technology described in Patent Documents 1 and 2 may not be sufficient to suppress haze as described above. Prior art literature
[0008] Japanese Patent Publication No. 2018-173621, Japanese Patent No. 4579728 The problem to be solved
[0009] The present invention is made under the circumstances described above and aims to provide a phase shift mask blank capable of sufficiently suppressing the occurrence of haze on the surface of a phase shift film, a phase shift mask with low haze defects, and a method for manufacturing the phase shift mask. means of solving the problem
[0010] The present invention is made to solve the above problem, and a phase shift mask blank according to one embodiment of the present invention is a phase shift mask blank used to produce a phase shift mask to which exposure light of a wavelength of 200 nm or less is applied, and comprises a transparent substrate and a phase shift film formed on the transparent substrate, wherein the phase shift film comprises a phase difference transmittance adjustment layer capable of adjusting a predetermined amount of phase and transmittance with respect to the transmitted exposure light, and a gas permeability protection layer formed on the phase difference transmittance adjustment layer and preventing gas permeation into the phase difference transmittance adjustment layer, wherein the phase difference transmittance adjustment layer is located on the side of the transparent substrate, and when the film thickness of the phase difference transmittance adjustment layer is denoted as d1 and the film thickness of the gas permeability protection layer is denoted as d2, d1 is thicker than d2 and d2 is 15 nm or less.
[0011] In addition, a phase shift mask according to one embodiment of the present invention is a phase shift mask having a circuit pattern to which an exposure light with a wavelength of 200 nm or less is applied, and comprises a transparent substrate and a phase shift film formed on the transparent substrate, wherein the phase shift film comprises a phase difference transmittance adjustment layer capable of adjusting a predetermined amount of phase and transmittance with respect to the transmitted exposure light, and a gas permeability protection layer formed on the phase difference transmittance adjustment layer and preventing gas permeation into the phase difference transmittance adjustment layer, wherein the phase difference transmittance adjustment layer is located on the side of the transparent substrate, and when the film thickness of the phase difference transmittance adjustment layer is denoted as d1 and the film thickness of the gas permeability protection layer is denoted as d2, d1 is thicker than d2 and d2 is 15 nm or less.
[0012] In addition, a method for manufacturing a phase shift mask according to one embodiment of the present invention is a method for manufacturing a phase shift mask using the phase shift mask blank described above, and is characterized by comprising the steps of: forming a light-shielding film on the phase shift film; forming a resist pattern on the light-shielding film formed on the phase shift film; forming a pattern on the light-shielding film using an oxygen-containing chlorine-based etching (Cl / O-based) after forming the resist pattern; forming a pattern on the phase shift film using a fluorine-based etching (F-based) after forming the pattern on the light-shielding film; removing the resist pattern after forming the pattern on the phase shift film; and removing the light-shielding film from the phase shift film using an oxygen-containing chlorine-based etching (Cl / O-based) after removing the resist pattern. Effects of the invention
[0013] By using a phase shift mask blank according to one embodiment of the present invention, the occurrence of haze on the mask can be sufficiently suppressed. Brief explanation of the drawing
[0014] FIG. 1 is a schematic cross-sectional view showing the configuration of a phase shift mask blank according to an embodiment of the present invention. FIG. 2 is a schematic cross-sectional view showing the configuration of a phase shift mask according to an embodiment of the present invention. FIG. 3 is a schematic cross-sectional diagram showing the manufacturing process of a phase shift mask using a phase shift mask blank according to an embodiment of the present invention. Specific details for implementing the invention
[0015] The inventors of the present invention believed that if all three elements—the constituent material of the phase adjustment film (the phase difference transmittance adjustment layer described below) constituting the phase shift mask blank or phase shift mask, an oxidizing gas such as water or oxygen, and exposure energy—are not present, the occurrence of haze in the mask blank or mask can be reduced, and thus the phase shift mask blank or phase shift mask was configured as follows. That is, the phase shift mask blank, phase shift mask, and the method of manufacturing the same according to the present embodiment are based on the technical concept of reducing the occurrence of haze by preventing the oxidizing gas from coming into contact with the constituent material of the phase adjustment film by providing a gas protection layer (so-called gas barrier layer) on the phase adjustment film.
[0016] A model for implementing the present invention will be described below with reference to the drawings. Additionally, the schematic cross-sectional view does not accurately reflect the actual dimensional ratios or the number of patterns, and the amount of penetration into the transparent substrate or the amount of damage to the film has been omitted.
[0017] Preferred embodiments of the phase shift mask blank of the present invention include the forms shown below.
[0018] (Overall configuration of the phase shift mask blank)
[0019] FIG. 1 is a schematic cross-sectional view showing the configuration of a phase shift mask blank according to an embodiment of the present invention. The phase shift mask blank (10) shown in FIG. 1 is a phase shift mask blank used to produce a phase shift mask to which an exposure light of a wavelength of 200 nm or less is applied, and comprises a substrate (hereinafter also simply referred to as "substrate") (11) that is transparent to the exposure wavelength, and a phase shift film (14) formed on the substrate (11). Additionally, the phase shift film (14) is provided with at least a phase difference transmittance adjustment layer (hereinafter simply referred to as "phase layer") (12)) which allows for adjusting a predetermined amount of phase and transmittance with respect to the transmitted exposure light, and a gas permeability protection layer (hereinafter simply referred to as "protection layer") (13) formed on the phase difference transmittance adjustment layer (12) and preventing gas permeation into the phase difference transmittance adjustment layer (12), and the phase layer (12) is located on the substrate (11) side. Additionally, when the film thickness of the phase layer (12) is denoted as d1 and the film thickness of the protection layer (13) is denoted as d2, d1 is thicker than d2, and d2 is 15 nm or less.
[0020] Hereinafter, each layer constituting the phase shift mask blank (10) according to an embodiment of the present invention will be described in detail.
[0021] (Circuit board)
[0022] There are no special restrictions on the substrate (11), and as the substrate (11), for example, quartz glass, CaF2, or aluminosilicate glass are generally used.
[0023] (Phase shift membrane)
[0024] The phase shift film (14) is provided with a phase layer (12) and a protection layer (13) in this order, and is formed on a substrate (11) with or without interposing another film.
[0025] The phase shift film (14) is a film that is resistant to, for example, oxygen-containing chlorine-based etching (Cl / O system) and can also be etched by fluorine-based etching (F system).
[0026] The transmittance value of the phase shift film (14) is, for example, within a range of 3% to 80% with respect to the transmittance of the substrate (11), and it is possible to appropriately select the optimal transmittance according to the desired wafer pattern. In addition, the phase difference value of the phase shift film (14) is, for example, within a range of 160 degrees to 220 degrees, and it is more preferable if it is within a range of 175 degrees to 190 degrees. That is, the phase shift film (14) may have a transmittance to the exposure light within a range of 3% to 80% and a phase difference within a range of 160 degrees to 220 degrees. If the transmittance of the phase shift film (14) to the exposure light is less than 3%, good exposure performance may not be obtained. In addition, if the phase difference is within a range of 160 degrees to 220 degrees, the required exposure performance can be easily maintained.
[0027] Phase Layer
[0028] The phase layer (12) is formed on the substrate (11) with or without interposing another film, and is a layer capable of adjusting a predetermined amount of phase and transmittance with respect to the transmitted exposure light. Here, "adjusting the phase" means, for example, reversing the phase. Also, "transmittance" means transmittance with respect to the exposure light.
[0029] The phase layer (12) is, for example, a single layer containing silicon and also containing at least one selected from transition metals, nitrogen, oxygen, and carbon, or a multilayer film or gradient film thereof, and the transmittance and phase difference with respect to the exposure wavelength are adjusted by appropriately selecting the composition and film thickness.
[0030] In terms of the elemental ratio of the entire phase layer (12), it is preferable that the phase layer (12) contains silicon in the range of 20 atomic% or more and 60 atomic% or less, and the transition metal in the range of 0 atomic% or more and 20 atomic% or less, and the nitrogen in the range of 30 atomic% or more and 80 atomic% or less, and the oxygen in the range of 0 atomic% or more and 30 atomic% or less, and the carbon in the range of 0 atomic% or more and 10 atomic% or less. The more desirable range of the content of each element in the phase layer (12) is, in terms of the element ratio of the entire phase layer (12), silicon is in the range of 30 atomic% or more and 50 atomic% or less, transition metal is in the range of 0 atomic% or more and 10 atomic% or less, nitrogen is in the range of 40 atomic% or more and 70 atomic% or less, oxygen is in the range of 0 atomic% or more and 20 atomic% or less, and carbon is in the range of 0 atomic% or more and 5 atomic% or less. If the content of each element in the phase layer (12) is within the above numerical range, the phase difference can be easily controlled along with the transmittance of the phase layer (12).
[0031] Additionally, the phase layer (12) may contain at least one of the oxides, carbides, and nitrides of the metal silicide. In that case, the metal constituting the metal silicide may be the transition metal described above.
[0032] The transition metal contained in the phase layer (12) is preferably at least one selected from molybdenum, titanium, vanadium, cobalt, nickel, zirconium, niobium, and hafnium, and is more preferably molybdenum. If the transition metal contained in the phase layer (12) is at least one selected from molybdenum, titanium, vanadium, cobalt, nickel, zirconium, niobium, and hafnium, the processing of the phase layer (12) becomes easier, and if it is molybdenum, the processability of the phase layer (12), such as etching, is further improved.
[0033] When the film thickness of the top layer (12) is denoted as d1 and the film thickness of the protective layer (13) is denoted as d2, the film thickness d1 of the top layer (12) is thicker than the film thickness d2 of the protective layer (13), and the film thickness d2 of the protective layer (13) is 15 nm or less. In addition, if the film thickness d2 of the protective layer (13) is made thicker than 15 nm, there is a possibility that it will be affected in terms of optical properties or crystal properties.
[0034] In addition, the film thickness d1 of the phase layer (12) may be thicker than 15 nm. When the film thickness d1 of the phase layer (12) is thicker than 15 nm, it becomes easier to adjust the phase and transmittance.
[0035] In addition, the total film thickness of the phase layer (12) and the protective layer (13) is preferably 50 nm or more, and more preferably 70 nm or more. If the total film thickness of the phase layer (12) and the protective layer (13) is within the above numerical range, it becomes easier to set the function of the phase shift film (14) to a desired value.
[0036] <Protection Layer>
[0037] The protective layer (13) is formed on the phase layer (12) with or without interposing another film, and is a layer for blocking and suppressing gas permeation into the phase layer (12) (in particular, permeation of oxidizing gases such as water or oxygen), i.e., a gas barrier layer. In this embodiment, since the intrusion of gas into the phase layer (12), which is considered one of the factors causing haze, can be blocked and suppressed, in the case where the mask is used for a long period of time (for example, when the dose amount on the mask is 100 kJ / cm² 2 Even when exceeding ) the occurrence of haze on the surface of the phase shift mask can be prevented or suppressed.
[0038] In addition, the gas (atmosphere gas) whose permeability is blocked or inhibited in the protective layer (13) is an oxidizing gas, specifically an oxygen-containing molecule, and more specifically a water molecule.
[0039] The protective layer (13) is preferably resistant to oxygen-containing chlorine-based (Cl / O-based) gas etching, etchable with fluorine-based gas (F-based), and can be modified by EB (electron beam) modification.
[0040] The protective layer (13) is preferably a single layer or a mixture of these compounds or a multilayer layer composed of one or more compounds selected from tantalum metal, tantalum compound, tungsten metal, tungsten compound, tellurium metal, and tellurium compound, but the composition is not particularly limited as long as it is a layer having a barrier function. In addition, the tantalum metal, tungsten metal, and tellurium metal mentioned above refer to individual parts of each metal.
[0041] The protective layer (13) made of a tantalum compound is a single layer or a multiple layer or gradient film containing one or more elements selected from tantalum, oxygen, nitrogen, and carbon.
[0042] The protective layer (13) made of a tantalum compound preferably contains tantalum in the range of 10 atomic% to 90 atomic% in the total elemental ratio of the protective layer (13), oxygen in the range of 0 atomic% to 90 atomic%, nitrogen in the range of 0 atomic% to 70 atomic%, and carbon in the range of 0 atomic% to 20 atomic%. The more preferred range of content for each element in the protective layer (13) made of a tantalum compound is, in the total elemental ratio of the protective layer (13), tantalum in the range of 20 atomic% to 80 atomic%, oxygen in the range of 0 atomic% to 80 atomic%, nitrogen in the range of 0 atomic% to 60 atomic%, and carbon in the range of 0 atomic% to 10 atomic%. If the content of each element in the protective layer (13) made of tantalum compound is within the above numerical range, the barrier effect of gas permeation to the phase layer (12) of the protective layer (13) is increased.
[0043] Additionally, the protective layer (13) made of a tungsten compound is a single layer containing tungsten and one or more elements selected from oxygen, nitrogen, and carbon, or a multilayer film thereof, or a gradient film.
[0044] The protective layer (13) made of a tungsten compound preferably contains tungsten in the range of 10 atomic% to 70 atomic% in the total elemental ratio of the protective layer (13), oxygen in the range of 30 atomic% to 90 atomic%, nitrogen in the range of 0 atomic% to 20 atomic%, and carbon in the range of 0 atomic% to 20 atomic%. A more preferred range of content for each element in the protective layer (13) made of a tungsten compound is, in the total elemental ratio of the protective layer (13), tungsten in the range of 20 atomic% to 60 atomic%, oxygen in the range of 50 atomic% to 80 atomic%, nitrogen in the range of 0 atomic% to 10 atomic%, and carbon in the range of 0 atomic% to 10 atomic%. If the content of each element in the protective layer (13) made of a tungsten compound is within the above numerical range, the barrier to gas permeation to the phase layer (12) of the protective layer (13) is increased.
[0045] Additionally, the protective layer (13) made of a tellurium compound is a single layer containing one or more elements selected from tellurium, oxygen, nitrogen, and carbon, or a multilayer film or gradient film.
[0046] The protective layer (13) made of a tellurium compound preferably contains tellurium in the range of 20 atomic% to 70 atomic% in the total elemental ratio of the protective layer (13), preferably contains oxygen in the range of 30 atomic% to 90 atomic%, preferably contains nitrogen in the range of 0 atomic% to 20 atomic%, and preferably contains carbon in the range of 0 atomic% to 20 atomic%. The more preferred range of content for each element in the protective layer (13) made of a tellurium compound is, in the total elemental ratio of the protective layer (13), that tellurium is in the range of 30 atomic% to 60 atomic%, oxygen is in the range of 50 atomic% to 80 atomic%, nitrogen is in the range of 0 atomic% to 10 atomic%, and carbon is in the range of 0 atomic% to 10 atomic%. If the content of each element in the protective layer (13) made of a tellurium compound is within the above numerical range, the barrier to gas permeation to the phase layer (12) of the protective layer (13) is increased.
[0047] As described above, if the protective layer (13) is a single layer or a mixture of the compounds selected from one or more compounds from tantalum metal, tantalum compound, tungsten metal, tungsten compound, tellurium metal, and tellurium compound, or a multilayer layer, gas permeation into the phase layer (12) can be effectively prevented.
[0048] In addition, the film thickness d2 of the protective layer (13) is 15 nm or less as described above, but if the film thickness d2 of the protective layer (13) is within the above numerical range, the barrier properties for gas transmission to the phase layer (12) can be maintained while maintaining optical properties or modification properties.
[0049] (Overall configuration of the phase shift mask)
[0050] Hereinafter, the configuration of the phase shift mask (100) according to an embodiment of the present invention will be described.
[0051] FIG. 2 is a schematic cross-sectional view showing the configuration of a phase shift mask according to an embodiment of the present invention. The phase shift mask (100) shown in FIG. 2 is a phase shift mask (i.e., a patterned phase shift mask) to which exposure light with a wavelength of 200 nm or less is applied and which has a circuit pattern, and comprises a substrate (11) that is transparent to the exposure wavelength and a phase shift film (14) formed on the substrate (11). In addition, the phase shift film (14) comprises at least a phase layer (12) that allows a predetermined amount of phase and transmittance to be adjusted respectively with respect to the transmitted exposure light, and a protective layer (13) formed on the phase layer (12) and which prevents gas transmission to the phase layer (12), and the phase layer (12) is located on the substrate (11) side. In addition, when the film thickness of the top layer (12) is denoted as d1 and the film thickness of the protective layer (13) is denoted as d2, d1 is thicker than d2, and d2 is 15 nm or less.
[0052] The phase shift mask (100) has a phase shift film pattern (17) formed by removing a portion of the phase shift film (14) to expose the surface of the substrate (11).
[0053] In addition, since the composition of each layer constituting the phase shift mask (100) according to the embodiment of the present invention is the same as the composition of each layer constituting the phase shift mask blank (10) according to the embodiment of the present invention described above, a detailed description of the composition of each layer is omitted.
[0054] (Method for manufacturing a phase-shift mask blank)
[0055] A method for manufacturing a phase shift mask (100) using a phase shift mask blank (10) according to the present embodiment comprises: a process of forming a light-blocking film (15) on a phase shift film (14); a process of forming a resist pattern (16) on the light-blocking film (15) formed on the phase shift film (14); a process of forming a pattern on the light-blocking film (15) with an oxygen-containing chlorine-based etching (Cl / O system) after forming the resist pattern (16); a process of forming a pattern on the phase shift film (14) with a fluorine-based etching (F system) after forming the pattern on the light-blocking film (15); a process of removing the resist pattern (16) after forming the pattern on the phase shift film (14); and a process of removing the light-blocking film (15) from the phase shift film (14) with an oxygen-containing chlorine-based etching (Cl / O system) after removing the resist pattern (16).
[0056] Here, a light-blocking film (15) according to an embodiment of the present invention is described.
[0057] Sunshade
[0058] The light-blocking film (15) is a layer formed on the phase shift mask blank (10) (protection layer (13)) according to the embodiment of the present invention described above.
[0059] The light-blocking film (15) is, for example, a single layer made of chromium, or a chromium compound, or a multilayer film made of the same, or a gradient film. More specifically, the light-blocking film (15) made of a chromium compound is a single layer containing chromium and one or more elements selected from nitrogen and oxygen, or a multilayer film made of the same, or a gradient film.
[0060] A light-shielding film (15) made of a chromium compound preferably contains chromium in the range of 30 atomic% or more and 100 atomic% or less in the total elemental ratio of the light-shielding film (15), preferably contains oxygen in the range of 0 atomic% or more and 50 atomic% or less, preferably contains nitrogen in the range of 0 atomic% or more and 50 atomic% or less, and preferably contains carbon in the range of 0 atomic% or more and 10 atomic% or less. A more preferred range of content for each element in the light-shielding film (15) made of a chromium compound is, in the total elemental ratio of the light-shielding film (15), chromium in the range of 50 atomic% or more and 100 atomic% or less, oxygen in the range of 0 atomic% or more and 40 atomic% or less, nitrogen in the range of 0 atomic% or more and 40 atomic% or less, and carbon in the range of 0 atomic% or more and 5 atomic% or less. If the content of each element in the light-blocking film (15) made of a chromium compound is within the above numerical range, the light-blocking ability of the light-blocking film (15) is increased.
[0061] The thickness of the light-blocking film (15) is preferably in the range of, for example, 35 nm or more and 80 nm or less, particularly in the range of 40 nm or more and 75 nm or less.
[0062] The light-blocking film (15) can be formed by a known method. As the easiest method to obtain a film with excellent homogeneity, the sputtering method is preferably cited, but in this embodiment, it is not necessary to limit it to the sputtering method.
[0063] The target and sputter gas are selected based on the film composition. For example, as a method for depositing a film containing chromium, reactive sputtering can be performed using a chromium-containing target in an inert gas such as argon, a reactive gas such as oxygen, or a mixed gas of inert and reactive gases. The flow rate of the sputter gas can be adjusted according to the film characteristics and may be kept constant during deposition; if it is desired to vary the amount of oxygen or nitrogen in the thickness direction of the film, it may be varied according to the desired composition. Additionally, the applied power to the target, the distance between the target and the substrate, and the pressure inside the deposition chamber may be adjusted.
[0064] Hereinafter, each process of the method for manufacturing a phase shift mask (100) according to an embodiment of the present invention will be described in detail.
[0065] FIG. 3 is a cross-sectional schematic diagram showing the manufacturing process of a phase shift mask (100) using the phase shift mask blank (10) shown in FIG. 1. FIG. 3(a) shows a process of forming a light-blocking film (15) on a phase shift film (14). FIG. 3(b) shows a process of applying a resist film on the light-blocking film (15), performing drawing, and then performing a developing process to form a resist pattern (16). FIG. 3(c) shows a process of patterning the light-blocking film (15) by oxygen-containing chlorine-based dry etching (Cl / O-based) along the resist pattern (16). FIG. 3(d) shows a process of patterning the phase shift film (14) by fluorine-based etching (F-based) along the pattern of the light-blocking film (15) to form a phase shift film pattern (17). FIG. 3(e) shows a cleaning process after peeling off the resist pattern (16). FIG. 3(f) shows a process of removing the light-blocking film (15) from the phase shift film (14) on which the phase shift film pattern (17) is formed using an oxygen-containing chlorine-based etching (Cl / O-based). In this way, a phase shift mask (100) according to the present embodiment is manufactured.
[0066] The phase shift mask (100) according to the present embodiment is a phase shift mask to which exposure light with a wavelength of 200 nm or less is applied, and comprises a substrate (11) and a phase shift film (14) formed on the substrate (11) with or without interposing another film. In addition, the phase shift film (14) comprises a phase layer (12) that allows for the adjustment of a predetermined amount of phase and transmittance with respect to the transmitted exposure light, and a protective layer (13) formed on the phase layer (12) and preventing gas transmission to the phase layer (12), and the phase layer (12) is located on the side of the substrate (11). In addition, the phase shift mask (100) comprises a phase shift film pattern (17) formed by removing a part of the phase shift film (14) so that a part of the substrate (11) is exposed. And, when the film thickness of the top layer (12) is denoted as d1 and the film thickness of the protective layer (13) is denoted as d2, the film thickness d1 of the top layer (12) is thicker than the film thickness d2 of the protective layer (13), and the film thickness d2 of the protective layer (13) is 15 nm or less.
[0067] In the process of FIG. 3(b), as the material for the resist film, either a positive-type resist or a negative-type resist may be used, but it is preferable to use a chemically amplified resist for electron beam lithography that enables the formation of high-precision patterns. The film thickness of the resist film is, for example, within a range of 50 nm or more and 250 nm or less. In particular, when fabricating a phase shift mask requiring fine pattern formation, it is necessary to thin the resist film so that the aspect ratio of the resist pattern (16) does not increase in order to prevent pattern collapse, and a film thickness of 200 nm or less is preferred. Meanwhile, the lower limit of the film thickness of the resist film is determined by comprehensively considering conditions such as the etching resistance of the resist material used, and 60 nm or more is preferred. When a chemically amplified type for electron beam lithography is used as the resist film, the energy density of the electron beam during lithography is 35 μC / cm²2 to 100μC / cm 2 It is within the range, and after this drawing, heat treatment and development treatment are performed to obtain a resist pattern (16).
[0068] In addition, in the process of Fig. 3 (e), the removal of the resist pattern (16) may be wet peeling with a peeling solution or dry peeling by dry etching.
[0069] In addition, in the process of (c) of FIG. 3, the conditions for oxygen-containing chlorine-based dry etching (Cl / O system) for patterning the light-blocking film (15) made of chromium alone or a chromium compound may be known ones that have been used for removing chromium compound films, and in addition to chlorine gas and oxygen gas, inert gases such as nitrogen gas or helium gas may be mixed as needed. Since the lower phase shift film (14) has resistance to oxygen-containing chlorine-based dry etching (Cl / O system), it remains without being removed or patterned in this process.
[0070] In addition, in the process of FIG. 3(d), the conditions for the fluorine-based dry etching (F-based) used to pattern the phase shift film (14) may be known ones that have been used for dry etching silicon-based compound films, tantalum compound films, or molybdenum compound films, and as for the fluorine-based gas, CF4, C2F6, or SF6 are common, and if necessary, active gases such as oxygen or inert gases such as nitrogen or helium may be mixed. In the case of FIG. 3(d), the upper layer light-shielding film (15) or resist pattern (16) is resistant to the fluorine-based dry etching (F-based), so it remains without being removed or patterned in this process. In FIG. 3(d), it is common to simultaneously cut the substrate (11) to a depth of about 1 nm to 3 nm to prevent defects in the phase shift film (14) and to perform fine adjustment of the phase difference.
[0071] In addition, in the process of (f) of FIG. 3, the conditions for the oxygen-containing chlorine-based dry etching (Cl / O system) used to remove the light-blocking film (15) may be known ones that have been used to remove chromium compound films, and in addition to chlorine gas and oxygen gas, inert gases such as nitrogen gas or helium gas may be mixed as needed. Since both the lower phase shift film (14) and the substrate (11) are resistant to the oxygen-containing chlorine-based dry etching (Cl / O system), they remain without being removed or patterned in this process.
[0072] [Example]
[0073] The embodiments of the present invention will be described more specifically below by way of examples, but the present invention is not limited to the following examples.
[0074] (Example 1)
[0075] A topological layer composed of silicon, molybdenum, oxygen, and nitrogen was deposited to a thickness of 65 nm using a DC sputtering device with two targets on a quartz substrate. Molybdenum and silicon were used as targets, and argon, oxygen, and nitrogen were used as sputtering gases. The composition of this topological layer was analyzed by ESCA and found to be Si:Mo:O:N = 30:5:20:45 (atomic % ratio).
[0076] A protective layer composed of tantalum and oxygen was deposited to a thickness of 8 nm on this phase layer using a DC sputtering device. Tantalum was used as the target, and argon and oxygen were used as the sputtering gases. The composition of this protective layer was analyzed by ESCA and found to be Ta:O = 30:70 (atomic % ratio).
[0077] In addition, the phase shift film composed of the phase layer and the protective layer formed in this way had a transmittance of 6% for exposure light and a phase difference of 180 degrees.
[0078] Next, a light-shielding film composed of chromium, oxygen, and nitrogen was deposited to a thickness of 50 nm on this protective layer using a DC sputtering device. Chromium was used as the target, and argon, oxygen, and nitrogen were used as the sputtering gases. The composition of this light-shielding film was analyzed by ESCA and found to be Cr:O:N = 55:35:10 (atomic % ratio).
[0079] Next, a negative chemically amplified electron beam resist is spin-coated onto this light-shielding film to a film thickness of 200 nm, and a pattern is formed at a dose of 35 μC / cm² 2 Electron beam lithography was performed, heat treatment was carried out at 110°C for 10 minutes, and development was performed by puddle development for 90 seconds to form a resist pattern.
[0080] Next, the light-blocking film was patterned using a dry etching device. Chlorine, oxygen, and helium were used as the etching gases, and the gas pressure was set to 5 mTorr, the ICP power to 400 W, and the bias power to 40 W. Over-etching was performed at 100%.
[0081] Next, a phase shift film composed of a protective layer and a phase layer was patterned using a dry etching apparatus. CF4 and oxygen were used as the etching gases, and the gas pressure was set to 5 mTorr, the ICP power to 400 W, and the bias power to 40 W. Dry etching was stopped when the quartz substrate was penetrated to an average of 3 nm.
[0082] Next, the resist pattern was stripped and cleaned by washing with sulfuric acid.
[0083] Next, the light-blocking film was removed using a dry etching apparatus. Chlorine, oxygen, and helium were used as the etching gas, and the gas pressure was set to 10 mTorr, the ICP power to 500 W, and the bias power to 10 W. Over-etching was performed at 200%. At this time, no damage occurred to the underlying phase shift film and the quartz substrate.
[0084] In this way, a phase shift mask for Example 1 was obtained.
[0085] Next, the dose amount at which haze was generated by accelerated exposure on this phase-shift mask was measured to be 135 kJ / cm² 2 It was.
[0086] The above "dose amount causing haze by accelerated exposure" means that the higher the value, the less likely haze is to occur. A dose amount of 70 kJ / cm² 2 If this is the case, there is absolutely no problem in using a phase shift mask, and the dose is 100kJ / cm² 2 If so, it can be said to be a phase shift mask where haze is extremely unlikely to occur.
[0087] From the above measurement results, if the phase shift mask is of Example 1, the dose amount is 135 kJ / cm² 2 Therefore, it has been confirmed that the occurrence of haze can be reduced.
[0088] (Example 2)
[0089] A topological layer consisting of silicon, molybdenum, oxygen, and nitrogen was deposited to a thickness of 67 nm using a DC sputtering device with two targets on a quartz substrate. Molybdenum and silicon were used as targets, and argon, oxygen, and nitrogen were used as sputtering gases. The composition of this topological layer was analyzed by ESCA and found to be Si:Mo:O:N = 35:5:15:45 (atomic % ratio).
[0090] A protective layer composed of tungsten and oxygen was deposited to a thickness of 5 nm on this phase layer using a DC sputtering device. Tungsten was used as the target, and argon and oxygen were used as the sputtering gases. The composition of this protective layer was analyzed by ESCA and found to be W:O = 25:75 (atomic % ratio).
[0091] In addition, the phase shift film composed of the phase layer and the protective layer formed in this way had a transmittance of 6% for exposure light and a phase difference of 180 degrees.
[0092] Next, a light-shielding film composed of chromium, oxygen, and nitrogen was deposited to a thickness of 50 nm on this protective layer using a DC sputtering device. Chromium was used as the target, and argon, oxygen, and nitrogen were used as the sputtering gases. The composition of this light-shielding film was analyzed by ESCA and found to be Cr:O:N = 55:35:10 (atomic % ratio).
[0093] Next, a negative chemically amplified electron beam resist is spin-coated onto this light-shielding film to a film thickness of 200 nm, and a pattern is formed at a dose of 35 μC / cm² 2 Electron beam lithography was performed, heat treatment was carried out at 110°C for 10 minutes, and development was performed by puddle development for 90 seconds to form a resist pattern.
[0094] Next, the light-blocking film was patterned using a dry etching device. Chlorine, oxygen, and helium were used as the etching gases, and the gas pressure was set to 5 mTorr, the ICP power to 400 W, and the bias power to 40 W. Over-etching was performed at 100%.
[0095] Next, a phase shift film composed of a protective layer and a phase layer was patterned using a dry etching apparatus. CF4 and oxygen were used as the etching gases, and the gas pressure was set to 5 mTorr, the ICP power to 400 W, and the bias power to 40 W. Dry etching was stopped when the quartz substrate was penetrated to an average of 3 nm.
[0096] Next, the resist pattern was stripped and cleaned by washing with sulfuric acid.
[0097] Next, the light-blocking film was removed using a dry etching apparatus. Chlorine, oxygen, and helium were used as the etching gas, and the gas pressure was set to 10 mTorr, the ICP power to 500 W, and the bias power to 10 W. Over-etching was performed at 200%. At this time, no damage occurred to the underlying phase shift film and the quartz substrate.
[0098] In this way, a phase shift mask for Example 2 was obtained.
[0099] Next, the dose amount at which haze was generated by accelerated exposure on this phase-shift mask was measured to be 92 kJ / cm² 2 It was.
[0100] From the above results, if the phase shift mask of Example 2 is used, the dose amount is 92 kJ / cm² 2 Therefore, it has been confirmed that the occurrence of haze can be reduced.
[0101] (Example 3)
[0102] A topological layer composed of silicon, molybdenum, oxygen, and nitrogen was deposited to a thickness of 67 nm using a DC sputtering device with two targets on a quartz substrate. Molybdenum and silicon were used as targets, and argon, oxygen, and nitrogen were used as sputtering gases. The composition of this topological layer was analyzed by ESCA and found to be Si:Mo:O:N=40:8:7:45 (atomic % ratio).
[0103] A protective layer composed of tellurium and oxygen was deposited to a thickness of 3 nm on this topological layer using a DC sputtering device. Tellurium was used as the target, and argon and oxygen were used as the sputtering gases. The composition of this protective layer was analyzed by ESCA and found to be Te:O = 35:65 (atomic % ratio).
[0104] In addition, the phase shift film composed of the phase layer and the protective layer formed in this way had a transmittance of 6% for exposure light and a phase difference of 180 degrees.
[0105] Next, a light-shielding film composed of chromium, oxygen, and nitrogen was deposited to a thickness of 50 nm on this protective layer using a DC sputtering device. Chromium was used as the target, and argon, oxygen, and nitrogen were used as the sputtering gases. The composition of this light-shielding film was analyzed by ESCA and found to be Cr:O:N = 55:35:10 (atomic % ratio).
[0106] Next, a negative chemically amplified electron beam resist is spin-coated onto this light-shielding film to a film thickness of 200 nm, and a pattern is formed at a dose of 35 μC / cm² 2 Electron beam lithography was performed, heat treatment was carried out at 110°C for 10 minutes, and development was performed by puddle development for 90 seconds to form a resist pattern.
[0107] Next, the light-blocking film was patterned using a dry etching device. Chlorine, oxygen, and helium were used as the etching gases, and the gas pressure was set to 5 mTorr, the ICP power to 400 W, and the bias power to 40 W. Over-etching was performed at 100%.
[0108] Next, a phase shift film composed of a protective layer and a phase layer was patterned using a dry etching apparatus. CF4 and oxygen were used as the etching gases, and the gas pressure was set to 5 mTorr, the ICP power to 400 W, and the bias power to 40 W. Dry etching was stopped when the quartz substrate was penetrated to an average of 3 nm.
[0109] Next, the resist pattern was stripped and cleaned by washing with sulfuric acid.
[0110] Next, the light-blocking film was removed using a dry etching apparatus. Chlorine, oxygen, and helium were used as the etching gas, and the gas pressure was set to 10 mTorr, the ICP power to 500 W, and the bias power to 10 W. Over-etching was performed at 200%. At this time, no damage occurred to the underlying phase shift film and the quartz substrate.
[0111] In this way, a phase shift mask for Example 3 was obtained.
[0112] Next, the dose amount at which haze was generated by accelerated exposure on this phase-shift mask was measured to be 87 kJ / cm² 2 It was.
[0113] From the above results, if the phase shift mask of Example 3 is used, the dose amount is 87 kJ / cm²2 Therefore, it has been confirmed that the occurrence of haze can be reduced.
[0114] (Example 4)
[0115] A topological layer composed of silicon, molybdenum, oxygen, and nitrogen was deposited to a thickness of 70 nm using a DC sputtering device with two targets on a quartz substrate. Molybdenum and silicon were used as targets, and argon, oxygen, and nitrogen were used as sputtering gases. The composition of this topological layer was analyzed by ESCA and found to be Si:Mo:O:N = 35:5:15:45 (atomic % ratio).
[0116] A protective layer consisting of tantalum, oxygen, and nitrogen was deposited to a thickness of 2 nm on this phase layer using a DC sputtering device. Tantalum was used as the target, and argon, oxygen, and nitrogen were used as the sputtering gases. The composition of this protective layer was analyzed by ESCA and found to be Ta:O:N = 65:5:30 (atomic % ratio).
[0117] In addition, the phase shift film composed of the phase layer and the protective layer formed in this way had a transmittance of 6% for exposure light and a phase difference of 180 degrees.
[0118] Next, a light-shielding film composed of chromium, oxygen, and nitrogen was deposited to a thickness of 50 nm on this protective layer using a DC sputtering device. Chromium was used as the target, and argon, oxygen, and nitrogen were used as the sputtering gases. The composition of this light-shielding film was analyzed by ESCA and found to be Cr:O:N = 55:35:10 (atomic % ratio).
[0119] Next, a negative chemically amplified electron beam resist is spin-coated onto this light-shielding film to a film thickness of 200 nm, and a pattern is formed at a dose of 35 μC / cm² 2 Electron beam lithography was performed, heat treatment was carried out at 110°C for 10 minutes, and development was performed by puddle development for 90 seconds to form a resist pattern.
[0120] Next, the light-blocking film was patterned using a dry etching device. Chlorine, oxygen, and helium were used as the etching gases, and the gas pressure was set to 5 mTorr, the ICP power to 400 W, and the bias power to 40 W. Over-etching was performed at 100%.
[0121] Next, a phase shift film composed of a protective layer and a phase layer was patterned using a dry etching apparatus. CF4 and oxygen were used as the etching gases, and the gas pressure was set to 5 mTorr, the ICP power to 400 W, and the bias power to 40 W. Dry etching was stopped when the quartz substrate was penetrated to an average of 3 nm.
[0122] Next, the resist pattern was stripped and cleaned by washing with sulfuric acid.
[0123] Next, the light-blocking film was removed using a dry etching apparatus. Chlorine, oxygen, and helium were used as the etching gas, and the gas pressure was set to 10 mTorr, the ICP power to 500 W, and the bias power to 10 W. Over-etching was performed at 200%. At this time, no damage occurred to the underlying phase shift film and the quartz substrate.
[0124] In this way, a phase shift mask for Example 4 was obtained.
[0125] Next, the dose amount at which haze was generated by accelerated exposure on this phase-shift mask was measured to be 110 kJ / cm² 2 It was.
[0126] From the above results, if the phase shift mask of Example 4 is used, the dose amount is 110 kJ / cm² 2 Therefore, it has been confirmed that the occurrence of haze can be reduced.
[0127] (Comparative Example 1)
[0128] A topological layer composed of silicon, molybdenum, oxygen, and nitrogen was deposited to a thickness of 70 nm using a DC sputtering device with two targets on a quartz substrate. Molybdenum and silicon were used as targets, and argon, oxygen, and nitrogen were used as sputtering gases. The composition of this topological layer was analyzed by ESCA and found to be Si:Mo:O:N=40:8:7:45 (atomic % ratio).
[0129] Next, a light-shielding film composed of chromium, oxygen, and nitrogen was deposited to a thickness of 50 nm on this phase layer using a DC sputtering device. Chromium was used as the target, and argon, oxygen, and nitrogen were used as the sputtering gases. The composition of this light-shielding film was analyzed by ESCA and found to be Cr:O:N = 55:35:10 (atomic % ratio).
[0130] Next, a negative chemically amplified electron beam resist is spin-coated onto this light-shielding film to a film thickness of 200 nm, and a pattern is formed at a dose of 35 μC / cm² 2 Electron beam lithography was performed, heat treatment was carried out at 110°C for 10 minutes, and development was performed by puddle development for 90 seconds to form a resist pattern.
[0131] Next, the light-blocking film was patterned using a dry etching device. Chlorine, oxygen, and helium were used as the etching gases, and the gas pressure was set to 5 mTorr, the ICP power to 400 W, and the bias power to 40 W. Over-etching was performed at 100%.
[0132] Next, a phase shift film consisting only of a phase layer was patterned using a dry etching apparatus. CF4 and oxygen were used as the etching gas, and the gas pressure was set to 5 mTorr, the ICP power to 400 W, and the bias power to 40 W. Dry etching was stopped at the point where the quartz substrate was penetrated by an average of 3 nm.
[0133] Next, the resist pattern was stripped and cleaned by washing with sulfuric acid.
[0134] Next, the light-blocking film was removed using a dry etching apparatus. Chlorine, oxygen, and helium were used as the etching gas, and the gas pressure was set to 10 mTorr, the ICP power to 500 W, and the bias power to 10 W. Over-etching was performed at 200%. At this time, no damage occurred to the underlying phase shift film and the quartz substrate.
[0135] In this way, a phase shift mask for Comparative Example 1 was obtained. That is, the phase shift mask for Comparative Example 1 is a phase shift mask that does not have the protective layer formed in Examples 1 to 4.
[0136] Next, the dose amount at which haze was generated by accelerated exposure on this phase-shift mask was measured to be 58 kJ / cm² 2 It was.
[0137] From the above results, in the phase shift mask of Comparative Example 1, the dose amount is 58 kJ / cm 2 For this reason, it was confirmed that the occurrence of haze could not be sufficiently reduced.
[0138] As described above, it can be seen that forming a protective layer on the phase layer is effective in reducing the amount of haze generated in the phase shift mask.
[0139] Although the phase shift mask blank of the present invention and the phase shift mask produced using the same have been described above by way of the above embodiments, the above embodiments are merely examples for carrying out the present invention, and the present invention is not limited thereto. Furthermore, modifications to these embodiments are within the scope of the present invention, and it is obvious from the above description that various other embodiments are possible within the scope of the present invention. Industrial applicability
[0140] In the present invention, since the composition, film thickness, and layer structure of the phase shift mask blank and the manufacturing process and conditions of the phase shift mask using the same are selected within an appropriate range, it is possible to provide a phase shift mask with a fine pattern formed with high precision, corresponding to the manufacture of logic devices of 28 nm or less or memory devices of 30 nm or less. Explanation of the symbols
[0141] 10: Phase Shift Mask Blank 11: Substrate transparent to exposure wavelength (substrate) 12: Phase layer (phase difference transmittance adjustment layer) 13: Protective layer (gas permeable protective layer) 14: Phase shift membrane 15: Shade 16: Resist Pattern 17: Phase shift membrane pattern 100: Phase shift mask d1: Thickness of the top layer d2: Thickness of the protective layer
Claims
Claim 1 A phase shift mask blank used for fabricating a phase shift mask to which exposure light with a wavelength of 200 nm or less is applied, comprising a transparent substrate and a phase shift film formed on the transparent substrate, wherein the phase shift film comprises a phase difference transmittance adjustment layer capable of adjusting the phase and transmittance with respect to transmitted exposure light, and a gas permeability protection layer formed on the phase difference transmittance adjustment layer and preventing gas permeation into the phase difference transmittance adjustment layer, wherein the phase difference transmittance adjustment layer is located on the side of the transparent substrate, and when the film thickness of the phase difference transmittance adjustment layer is denoted as d1 and the film thickness of the gas permeability protection layer is denoted as d2, d1 is thicker than d2 and d2 is 15 nm or less, wherein the phase difference transmittance adjustment layer contains silicon, a transition metal, nitrogen, and oxygen, and the transition metal is molybdenum, titanium, vanadium, cobalt, nickel, zirconium, niobium, and A phase shift mask blank characterized by being at least one type selected from hafnium. Claim 2 A phase shift mask blank according to claim 1, characterized in that the phase shift film is resistant to oxygen-containing chlorine-based etching (Cl / O system) and can also be etched by fluorine-based etching (F system). Claim 3 delete Claim 4 A phase shift mask blank according to claim 1 or 2, wherein the gas permeable protective layer contains at least one selected from tantalum metal, tantalum compound, tungsten metal, tungsten compound, tellurium metal, and tellurium compound. Claim 5 A phase shift mask blank according to claim 4, wherein the tantalum compound contains at least one selected from tantalum, oxygen, nitrogen, and carbon. Claim 6 A phase shift mask blank according to claim 4, wherein the tungsten compound contains at least one selected from tungsten, oxygen, nitrogen, and carbon. Claim 7 A phase shift mask blank according to claim 4, wherein the tellurium compound contains at least one selected from tellurium, oxygen, nitrogen, and carbon. Claim 8 A phase shift mask having a circuit pattern to which an exposure light with a wavelength of 200 nm or less is applied, and comprises a transparent substrate and a phase shift film formed on the transparent substrate, wherein the phase shift film comprises a phase difference transmittance adjustment layer capable of adjusting the phase and transmittance with respect to the transmitted exposure light, and a gas permeability protection layer formed on the phase difference transmittance adjustment layer and preventing gas permeation into the phase difference transmittance adjustment layer, wherein the phase difference transmittance adjustment layer is located on the side of the transparent substrate, and when the film thickness of the phase difference transmittance adjustment layer is denoted as d1 and the film thickness of the gas permeability protection layer is denoted as d2, d1 is thicker than d2 and d2 is 15 nm or less, and the phase difference transmittance adjustment layer contains silicon, a transition metal, nitrogen, and oxygen, and the transition metal is selected from molybdenum, titanium, vanadium, cobalt, nickel, zirconium, niobium, and hafnium. A phase shift mask characterized by having at least one type. Claim 9 A phase shift mask according to claim 8, characterized in that the phase shift film is resistant to oxygen-containing chlorine-based etching (Cl / O system) and can also be etched by fluorine-based etching (F system). Claim 10 delete Claim 11 A phase shift mask according to claim 8 or 9, wherein the gas permeable protective layer contains at least one selected from tantalum metal, tantalum compound, tungsten metal, tungsten compound, tellurium metal, and tellurium compound. Claim 12 A phase shift mask according to claim 11, wherein the tantalum compound contains at least one selected from tantalum, oxygen, nitrogen, and carbon. Claim 13 A phase shift mask according to claim 11, characterized in that the tungsten compound contains at least one selected from tungsten, oxygen, nitrogen, and carbon. Claim 14 A phase shift mask according to claim 11, characterized in that the tellurium compound contains at least one selected from tellurium, oxygen, nitrogen, and carbon. Claim 15 A method for manufacturing a phase shift mask using a phase shift mask blank described in claim 1 or 2, comprising: a process of forming a light-shielding film on the phase shift film; a process of forming a resist pattern on the light-shielding film formed on the phase shift film; a process of forming a pattern on the light-shielding film using an oxygen-containing chlorine-based etching (Cl / O system) after forming the resist pattern; a process of forming a pattern on the phase shift film using a fluorine-based etching (F system) after forming the pattern on the light-shielding film; a process of removing the resist pattern after forming the pattern on the phase shift film; and a process of removing the light-shielding film from the phase shift film using an oxygen-containing chlorine-based etching (Cl / O system) after removing the resist pattern.
Citation Information
Patent Citations
Phase shift mask, method of manufacturing the same, and method of manufacturing semiconductor device
JP2011065113A
Method for manufacturing photomask
JP2015184453A
Method for manufacturing photomask
KR1020110126687A